Solution to Stewart Calculus
Answer
You should use the substitution rule. Let $u=e^z +z$. Then we have $$ du=(e^z +z)' dz=(e^z +1)dz$$ At $z=0$ we have $u=e^0 +0=1$ and at $z=1$ we have $u=e^1 +1=e+1$. So, after the substitution, the integral becomes $$\int _0 ^1 \frac {e^z +1}{e^z +z}\,dz=\int _1 ^{e+1}\frac{du}{u}=\ln|u|\,\Big]_1 ^{e+1} =\ln(e+1)-\ln(1)=\ln(e+1)-0=\ln(e+1)$$
Martin
1.6K
The answer is accepted.
Join Matchmaticians Affiliate Marketing
Program to earn up to a 50% commission on every question that your affiliated users ask or answer.
- accepted
- 768 views
- $10.00
Related Questions
- Why does $ \sum\limits_{n=1}^{\infty } 2^{2n} \times \frac{(n!)^2}{n(2n+1)(2n)!} =2 $ ?
- Let $z = f(x − y)$. Show that $\frac{\partial z}{\partial x}+\frac{\partial z}{\partial y}=0$
- Finding absolute and relative extrema given an equation.
- Find $\int x \sqrt{1-x}dx$
- Solve the attached problem
- Convergence of $\int_{1}^{\infty} e^{\sin(x)}\cdot\frac{\sin(x)}{x^2} $
- Explain parameter elimination for complex curves v2
- Answer is done but need help